A Review of 2625 Isolated Hydrocele Cases in Children - Atıcı, Ahmet; Erdoğan, Derya; Karaman, İbrahim; Karaman, Ayşe; Çavuşoğlu, Yusuf Hakan; Maden, Haşim Ata; Özgüner, İsmet Faruk; Yılmaz, Engin; Afşarlar, Çağatay Evrim (Iranian Journal of Pediatric Surgery, 2017)
Introduction: Inguinal hernias and hydroceles are the most frequently performed procedures in pediatric surgery departments. In this study, we aimed to define the spontaneous regression rate in different types of hydroceles, the regression age, the timing of surgery, and the optimal treatment approaches for each hydrocele type in cases with isolated hydroceles in children. Material &Methods: This historical cohort study included 2625 patients which were admitted between January 2004 and December 2012. The hydroceles were classified as: ‘non-communicating hydroceles’, ‘communicating hydroceles’, ‘spermatic cord hydroceles’ and ‘abdomino-scrotal hydroceles’ (ASH). Patients were divided into two groups with regard to their ages at diagnosis as follows: those presenting in the newborn period and before 24 months of age (Younger– Group 1) and those presenting after 24 months of age (Older – Group 2). Determining the type of isolated hydrocele, the decision making for follow-up or surgery, and the follow-up period were conducted by 7 attending pediatric surgeons and 6 residents. Results: In Group 1, 93% of 1086 non-communicating hydroceles, 40% of 158 cord hydroceles, and 15% of 34 communicating hydroceles resolved during the follow-up, and the remaining patients with each type of hydrocele underwent surgery. In Group 2, 8.7% of 183 non-communicating hydroceles resolved during the follow-up. Conclusion: The primary treatment of patients with isolated hydrocele should be decided regarding the type of hydrocele, along with age at admission, and accordingly, conservative or surgical treatment should be considered.